1994
DOI: 10.21273/hortsci.29.2.88
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Fertilizer Enhances Arsenic Uptake by Apricot Liners Grown in Lead-arsenate-enriched Soil

Abstract: Phosphate fertilizer additions to soils containing lead arsenate (LA) pesticide residues can increase As volubility. Apricot (Prunus armeniaca L.) rootstock liners were grown in nondraining pots containing Burch loam soil that received a factorial treatment combination: 1) LA enrichment [no added LA (-LA), and LA added at 138 mg Pb/kg and 50 mg As/kg (+LA)]; 2) fertilizer type [monoammonium phosphate (MAP) and its sulfur analog ammonium hydrogen sulfate (AHS)]; and 3) fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Decrease of PO 3− 4 to 0.014 mg l −1 increased arsenic accumulation by L. gibba by six-fold (significant at t-test p ≤ 0.05). The current results agree with finding in other studied where PO 3− 4 reduces the arsenic accumulation in plants, fungi and algae (Aracil et al, 2001;Barrachina et al, 1995;Creger and Peryea, 1994;Meharg and Hartley-Whitaker, 2002). The surface tailing waters in Neuensalz-Mechelgrün had considerably high dissolved oxygen (Table I), thus As V were probably the predominant species.…”
Section: Amendmentssupporting
confidence: 92%
“…Decrease of PO 3− 4 to 0.014 mg l −1 increased arsenic accumulation by L. gibba by six-fold (significant at t-test p ≤ 0.05). The current results agree with finding in other studied where PO 3− 4 reduces the arsenic accumulation in plants, fungi and algae (Aracil et al, 2001;Barrachina et al, 1995;Creger and Peryea, 1994;Meharg and Hartley-Whitaker, 2002). The surface tailing waters in Neuensalz-Mechelgrün had considerably high dissolved oxygen (Table I), thus As V were probably the predominant species.…”
Section: Amendmentssupporting
confidence: 92%
“…The changes in the As concentrations would be connected with replacement of the adsorbed AsO 4 ions by PO 4 ions (e.g. Creger and Pereyra 1994).…”
Section: Extractsmentioning
confidence: 99%
“…Adsorption of As on soil components can be substantially suppressed by application of phosphate as a consequence of competition for the adsorption sites between phosphate and As(V) (Creger and Pereyra 1994;Davenport and Pereyra 1991;Pereyra 1998). Smith et al (2002) observed a substantial reduction in the adsorption of As(III) in the presence of phosphate ions only for soils with low Fe oxide contents (< 100 mmol/kg).…”
Section: Introductionmentioning
confidence: 99%
“…This observation was attributed to the chemical similarity and addition of phosphates to the soil, possibly replacing the arsenate from the sorption sites (Wauchope and McDowell 1984;Peryea 1991). This action could possibly increase the availability of arsenic to the soil solution (Peryea and Kammereck 1997) and may thus enhance arsenate uptake by plants (Creger andPeryea 1994, Quaghebeur andRengel 2001). At comparable soil arsenic level, addition of phosphate caused higher availability of arsenic and phosphorus in soil and increased uptake by corn plants (Ho Man Leung et al 2010;Woolson et al 1973).…”
Section: Discussionmentioning
confidence: 99%